2014
DOI: 10.3184/174751914x14007821182269
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of 1,3-Dialkylimidazole-2-Selenones

Abstract: An efficient method for the synthesis of 1,3-dialkylimidazole-2-selenones involves the reaction of 1,3-dialkylimidazole salts with selenium in the presence of potassium carbonate in ethanol or acetone under refluxing conditions to afford the products in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…When the imidazolium salt 9 was reacted with two equivalents of the strong base KO t Bu, both Me 3 Si‐vinyl bonds were cleaved and the parent imidazole‐2‐selone 12 was quantitatively formed upon subsequent addition of black selenium to the reaction solution. Compound 12 has previously been prepared in a related procedure by reacting 1,3‐dimethylimidazolium chloride with selenium in the presence of bases [25] . The analytical data obtained for our product are consistent with the values reported there.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…When the imidazolium salt 9 was reacted with two equivalents of the strong base KO t Bu, both Me 3 Si‐vinyl bonds were cleaved and the parent imidazole‐2‐selone 12 was quantitatively formed upon subsequent addition of black selenium to the reaction solution. Compound 12 has previously been prepared in a related procedure by reacting 1,3‐dimethylimidazolium chloride with selenium in the presence of bases [25] . The analytical data obtained for our product are consistent with the values reported there.…”
Section: Resultssupporting
confidence: 86%
“…Compound 12 has previously been prepared in a related procedure by reacting 1,3-dimethylimidazolium chloride with selenium in the presence of bases. [25] The analytical data obtained for our product are consistent with the values reported there. The cleavage of both Si-vinyl bonds in our product is clearly indicated by the disappearance of the typical SiMe 3 lines at δ 1 H = 0-0.5 ppm and δ 13 C = 0-10 ppm and by the appearance of new signals characteristic of the HÀ C=CÀ H moiety at δ 1 H = 6.83 ppm and δ 13 C = 119.7 ppm.…”
Section: Reactivity Studiessupporting
confidence: 90%
“…Our previous studies found that HSe – had a strong reductive ability and could reduce SO 2 easily . In this study, inspired by the selenium-catalyzed reduction of organic compounds using CO, we suggest a new strategy to reduce SO 2 by CO using selenium as the catalyst in the liquid phase. A common polar aprotic and nonvolatile solvent DMF and H 2 O mixture solution was used as the solvent.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, we also have reported the synthesis of 1,3-dialkylimidazole-2-selenones using 1,3-dialkylimidazolium salts with selenium in water or in ethanol or acetone [16,17]. Keeping this result in mind, we reported 1,3-dialkylimidazole-2-selenone catalyzed oxidative carbonylation of aromatic amines with carbon monoxide in the presence of oxygen in ionic liquids (Scheme 1).…”
Section: Introductionmentioning
confidence: 90%